Fresno County Bar Association's Barristers Benefit Ball at the Fresno Metropolitan Museum - Watkins, Howard::::::::: (1988)
Susan Park, Brenda Hill, Hon. Brad Hill, Deborah Byron, Donald Black, Deborah Owdom, Bruce Owdom, and Gordon Park